Epidemiologic and Molecular Prognostic Review of Glioblastoma - Thakkar, Jigisha P.; Dolecek, Therese A.; Horbinski, Craig; Ostrom, Quinn T.; Lightner, Donita D.; Barnholtz-Sloan, Jill S.; Villano, John L. (Cancer epidemiology, biomarkers & prevention, 2014)
Glioblastoma multiforme (GBM) is the most common and aggressive primary central nervous system malignancy with a median survival of 15 months. The average incidence rate of GBM is 3.19/100,000 population, and the median age of diagnosis is 64 years. Incidence is higher in men and individuals of white race and non-Hispanic ethnicity. Many genetic and environmental factors have been studied in GBM, but the majority are sporadic, and no risk factor accounting for a large proportion of GBMs has been identified. However, several favorable clinical prognostic factors are identified, including younger age at diagnosis, cerebellar location, high performance status, and maximal tumor resection. GBMs comprise of primary and secondary subtypes, which evolve through different genetic pathways, affect patients at different ages, and have differences in outcomes. We report the current epidemiology of GBM with new data from the Central Brain Tumor Registry of the United States 2006 to 2010 as well as demonstrate and discuss trends in incidence and survival. We also provide a concise review on molecular markers in GBM that have helped distinguish biologically similar subtypes of GBM and have prognostic and predictive value. Cancer Epidemiol Biomarkers Prev; 23(10); 1985–96. ©2014 AACR.